Exploring humans' reactions to degraded natural environments through photographic stimuli - Dao, Truc Anh, author; Steger, Michael F., advisor; Dik, Bryan J., committee member; Aloise-Young, Patricia A., committee member; Goemans, Christopher G., committee member (Colorado State University. Libraries, 2021)
The discrepancy between the imminent threat of climate change and the public lack of meaningful response to that threat has been a puzzling phenomenon. One of the approaches proposed to answer the question about human behaviors regarding climate change is Terror Management Theory (TMT). TMT posits that human share a universal fear of death, such that once exposed, people will engage in some defense mechanisms to ward off those fears. One of those mechanisms involves reassuring oneself of possible symbolic or literal immortality by adhering to shared beliefs within a group, or cultural worldviews. Natural environments can be a source of existential threat to humans as they are inherently associated with both life and death. Therefore, confrontation with nature can provoke anxiety about death, which in turn motivates people to distance themselves from nature. This current project explored the effects of viewing images of different types of environments on people's thoughts of death and worldview defense behavior through four experimental studies. In the first and fourth study, participants viewed and wrote about one of three sets of seven randomly assigned images of the environment (i.e., intact nature, degraded nature, nature with visible human constructions). Participants' thoughts about mortality were assessed via a word completion task. In the second and third study, participants also viewed and wrote about seven images according to their conditions. Next, participants were told that they were going to read two brief essays written by foreign students about the United States. Half of the participants read a pro-American essay and the other half read an anti-American one. In prior studies, participants' reactions to the author of the essay were indicative of whether or not they engage in worldview defense. While data from the first study provided support for degraded nature increasing thoughts of death, the three subsequent studies presented mixed results. Future research on existential anxieties and their effects on people's response to threats might help further explore humans' climate change responses.